Are biofortified staple food crops improving vitamin A and iron status in women and children?: New evidence from efficacy trials - De Moura, Fabiana F.; Palmer, Amanda C.; Finkelstein, Julia L.; Haas, Jere D.; Murray-Kolb, Laura E.; Wenger, Michael J.; Birol, Ekin; Boy, Erick; Peña-Rosas, Juan Pablo (Elsevier, 2014)
Biofortification is the breeding of crops to increase their nutritional value, including increased contents of micronutrients or their precursors. Biofortification aims to increase nutrient levels in crops during plant growth rather than during processing of the crops into foods. Emerging research from 8 human trials conducted in the past decade with staple food crops that have been biofortified by traditional plant breeding methods were presented in this symposium. Specifically, data from 6 efficacy and 2 effectiveness trials were discussed to assess the effects of regular consumption of these enhanced staple crops on improving population vitamin A and iron status and reducing the burden of micronutrient deficiencies in targeted populations living in South Asia, Sub-Saharan Africa, and Latin America. Biofortified food crops appear to have a positive impact on nutritional and functional health outcomes, as the results from the trials suggest. Additional implementation research will be needed to ensure maximization of the beneficial impact of this intervention and a smooth scaling up to make biofortification a sustainable intervention in public health. The challenge for the global health community remains how to take this efficacious intervention and implement at large scale in the real world.